2009
DOI: 10.1002/cbic.200800636
|View full text |Cite
|
Sign up to set email alerts
|

Altering the Substrate Specificity of RhlI by Directed Evolution

Abstract: REDUCING VIRULENCE: RhlI catalyzes the synthesis of N-butanoyl homoserine lactone (BHL), with a minor product N-hexanoyl homoserine lactone (HHL). By using directed evolution and a genetic screen, RhlI has been engineered for enhanced production of both BHL and HHL at a similar level. Quorum sensing regulates biofilm formation and virulence factor production in the human opportunistic pathogen Pseudomonas aeruginosa. We used directed evolution to engineer RhlI, an enzyme in the RhlI-RhlR quorum-sensing system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Transcription factors involved in quorum sensing have been the target of extensive protein engineering efforts to accomplish such goals (Collins et al, 2005; Hawkins et al, 2007; Kambam et al, 2008, 2009). For example, by screening a large library of LuxR mutants, a library of transcription factors with up to a 100 fold increase in sensitivity to specific molecules was developed (Collins et al, 2005).…”
Section: Sensory Mechanisms To Determine the State Of The Cellmentioning
confidence: 99%
“…Transcription factors involved in quorum sensing have been the target of extensive protein engineering efforts to accomplish such goals (Collins et al, 2005; Hawkins et al, 2007; Kambam et al, 2008, 2009). For example, by screening a large library of LuxR mutants, a library of transcription factors with up to a 100 fold increase in sensitivity to specific molecules was developed (Collins et al, 2005).…”
Section: Sensory Mechanisms To Determine the State Of The Cellmentioning
confidence: 99%
“…The roles played by individual amino acid residues in the AHL synthase reaction are unclear, although mutagenesis studies of conserved and random residues have identified critical residues in RhlI [14, 15]. The pH-dependence of kinetic parameters in the RhlI reaction show that the ionization states of two residues are important for catalysis and binding [9].…”
Section: Bacterial Census: Ahl Synthesismentioning
confidence: 99%
“…In addition, these authors demonstrated how artificial positive feedback loops can increase the effective sensitivity of LuxR-based circuits. The signal synthase component of QS systems has also been engineered: the substrate specificity of the RhlI synthase was modified to increase production of the non-native signal hexanoyl-homoserine lactone [14]. …”
Section: Engineering Protein Transcription Factorsmentioning
confidence: 99%
“…A similar approach was used recently to generate a genetic AND gate using LuxR and LacI [14]. Ribosome binding sites (RBS) are good targets for tuning mismatches in component activities.…”
Section: Construction Of Synthetic Genetic Circuitsmentioning
confidence: 99%